Insulin degludec: a new basal insulin analogue with an ultra-long duration of action. Safety and efficacy in Russian patients with diabetes - Marina Vladimirovna Shestakova (Endocrinology Research Centre, 2015)
Aims. Insulin degludec (IDeg) is a novel insulin analogue that, following subcutaneous injection, forms soluble multihexamers, resulting in an ultra-long duration of action, which is two-fold longer than that of insulin glargine (IGlar). We present data from Russian cohorts of two multinational, open-label, treat-to-target phase 3 trials that investigated the efficacy and safety of IDeg and IGlar administered once daily.Materials and methods. The BEGIN Basal–Bolus Type 1 trial was a 52-week study comparing IDeg (n = 45) to IGlar (n = 16), both 100 U/mL, and in combination with insulin aspart in patients with type 1 diabetes (T1D). The BEGIN LOW VOLUME trial compared IDeg (200 U/mL; n = 27) to IGlar (100 U/mL; n = 28) over 26 weeks in insulin-naïve patients with type 2 diabetes (T2D) inadequately controlled with oral antidiabetic drugs. The primary outcome of both studies was the non-inferiority of IDeg to IGlar, as assessed by HbA1c level reduction at the trial end.Results. In patients with T1D, HbA1c level reductions at the trial end were 0.42% (IDeg) and 0.22% (IGlar). The rates of confirmed hypoglycaemia (plasma glucose level < 3.1 mmol/L or severe) were lower in IDeg than in IGlar [17.83 vs. 22.87 events/patient/year exposure (PYE), respectively]. The rates of nocturnal-confirmed hypoglycaemia were lower for IDeg than for IGlar (2.24 vs. 4.77 events/PYE, respectively). Severe episodes occurred in >10% of patients in both treatment groups, with rates per PYE of 0.12 (IDeg) and 0.06 (IGlar). In patients with T2D, HbA1c levels decreased by 1.17% (IDeg) and 1.26% (IGlar) at the trial end. The rates of confirmed hypoglycaemia were comparable in IDeg and IGlar (0.52 vs. 0.44 events/PYE, respectively). The rates of nocturnal-confirmed hypoglycaemia were lower for IDeg than for IGlar (0.18 vs. 0.28 events/PYE, respectively). No severe episode occurred in either treatment group. In both studies, IDeg was well tolerated with no difference in safety between the two analogues investigated.Conclusions. In both T1D and T2D, IDeg provided similar glycaemic control to IGlar, with a lower risk of nocturnal hypoglycaemia.